Collective behaviour of model microswimmers - Putz, V (2010)
At small length scales, low velocities, and high viscosity, the effects of inertia on motion through fluid become insignificant and viscous forces dominate. Microswimmer propulsion, of necessity, is achieved through different means than that achieved by macroscopic organisms. We describe in detail the hydrodynamics of microswimmers consisting of colloidal particles and their interactions. In particular we focus on two-bead swimmers and the effects of asymmetry on collective motion, calculating analytical formulae for time-averaged pair interactions and verifying them with microscopic time-resolved numerical simulation, finding good agreement. We then examine the long-term effects of a swimmer's passing on a passive tracer particle, finding that the force-free nature of these microswimmers leads to loop-shaped tracer trajectories. Even in the presence of Brownian motion, the loop-shaped structures of these trajectories can be recovered by averaging over a large enough sample size. Finally, we explore the phenomenon of synchronisation between microswimmers through hydrodynamic interactions, using the method of constraint forces on a force-based swimmer. We find that the hydrodynamic interactions between swimmers can alter the relative phase between them such that phase-locking can occur over the long term, altering their collective motion.